Temporal variations in suicide attempt rates: A hospital-based study from India - Shivanand Kattimani; Venkatalakshmi Penchilaiya; Siddharth Sarkar; V Muthukrishnan (Journal of Family Medicine and Primary Care, 2016)
Background: Temporal variations of suicide attempts can help to better understand correlates of suicidal behavior. This study attempted to find the diurnal, weekly, and seasonal variations in suicide attempts at a tertiary care hospital in India. Materials and Methods: This record-based study was conducted among patients evaluated at a crisis intervention clinic over a 4-year period at a tertiary care teaching hospital in Southern India. Patients who attempted suicide in recent past and had been medically stabilized were evaluated in this clinic. The distribution of suicide attempts across the time of the day, the day of the week, and month of the year was assessed. Results: Of the 407 patients who were included in the analysis, the frequency of suicide attempts varied across time of the day (χ2 = 134.504, P < 0.001). The most common period of the day for the attempt was evenings (6 pm to 9 pm). There were no significant temporal associations between month of the year or day of the week and suicide attempts though peaks were observed for June among the months and Sundays among days of the week. Conclusion: Diurnal variations exist in the suicide attempts. This has implications on clinical caseloads on emergency departments, especially during the times when staffing might be sub-optimal.